Hamas-Izrael War, Short Analysis of First Two Phases of War - Bordas, Maria (European Scientific Journal, ESJ, 2024)
At the end of 2023, Middle East faced new challenges. Among these new challenges, one of most important is the Hamas-Israel war. To understand the factors of Hamas operational success, and the strategic surprise attack on Israel from Gaza, on October 7, 2023, needs a thorough analysis to understand all its political, intelligence and operational failures aspects. In this article three issues related to new Gaza war will be addressed. Firstly, this article highlights the political background of the bloodiest attack in modern Israel's history happened on October 7, 2023. Secondly, this article seeks to answer the question, how was Hamas able to attack a country with operates one of the best intelligence organizations in the world by an extreme surprise? Finally, based upon the available data, this article analyzes the first and second phases of war.